Interest in Genetic Testing in Ashkenazi Jewish Parkinson's Disease Patients and Their Unaffected Relatives. Issue 2 (17th August 2014) - Gupte, Manisha; Alcalay, Roy N.; Mejia‐Santana, Helen; Raymond, Deborah; Saunders‐Pullman, Rachel; Roos, Ernest; Orbe‐Reily, Martha; Tang, Ming‐X; Mirelman, Anat; Ozelius, Laurie; Orr‐Urtreger, Avi; Clark, Lorraine; et al.
Abstract: Our objective was to explore interest in genetic testing among Ashkenazi Jewish (AJ) Parkinson's Disease (PD) cases and first‐degree relatives, as genetic testing for LRRK2 G2019S is widely available. Approximately 18 % of AJ PD cases carry G2019S mutations; penetrance estimations vary between 24 and 100 % by age 80. A Genetic Attitude Questionnaire (GAQ) was administered at two New York sites to PD families unaware of LRRK2 G2019S mutation status. The association of G2019S, age, education, gender and family history of PD with desire for genetic testing (outcome) was modeled using logistic regression. One‐hundred eleven PD cases and 77 relatives completed the GAQ. Both PD cases and relatives had excellent PD‐specific genetic knowledge. Among PD, 32.6 % "definitely" and 41.1 % "probably" wanted testing, if offered "now." Among relatives, 23.6 % "definitely" and 36.1 % "probably" wanted testing "now." Desire for testing in relatives increased incrementally based on hypothetical risk of PD. The most important reasons for testing in probands and relatives were: if it influenced medication response, identifying no mutation, and early prevention and treatment. In logistic regression, older age was associated with less desire for testing in probands OR = 0.921 95%CI 0.868–0.977, p  = 0.009. Both probands and relatives express interest in genetic testing, despite no link to current treatment or prevention.